Demographic and Clinical Profiles of PCR Positive Rickettsia felis Infected Patients at A Tertiary Care Hospital in Bangladesh - Ahmed, Rajib; Jahan, Tarana; Sharmi, Rumana Hasan; Begum, Habiba; Boby, Farzana; Rawnuck, Tanzila; Paul, Shyamal Kumar; Hossain, Muhammad Akram (Bangladesh Journal of Medical Microbiology, 2023)
Background: Rickettsial infections remain relatively unexplored, under recognized and under reported due to a lack of awareness and limited access to diagnosis. Objective: The purpose of the present study was to evaluate the demographic and clinical profile of PCR positive Rickettsia felis infected patients attended at a tertiary care hospital. Methodology: This cross-sectional study was conducted in the Department of Microbiology at Mymensingh Medical College, Mymensingh, Bangladesh from July 2013 to June 2014 for duration of one year. Patients with fever (102° to 104°F) more than 15 days of any age and gender, not responding to commonly used antibiotics and any other additional complaints and clinical features including headache, rash, lymphadenopathy or myalgia and eschars on the skin were included in this study. Patients with evident cause of fever like malaria diagnosed by blood smear or immunochromatography were excluded from the study. Blood was collected according to blood collection guidelines. PCR from blood was performed using standard protocol with specific primers to detect Rickettsia up to species level. Results: A total number of 50 respondents were recruited after fulfilling the inclusion and exclusion criteria. Among them 21(42%) cases were PCR positive. Among 21 PCR positive cases, the predominant age group was more than 15 to 30 years which was 11(52.4%), female patients were predominant than male patients which was 11(52.0%). All the cases with Rickettsial infection had fever 21(100.0%). Other associated features like headache was most commonly noticed in 10(47.6%) cases followed by body-ache, Cough and rash which was 7(33.3%) cases, 5(23.8%) cases and 1/21 (4.7%) cases respectively. Conclusion: This study demonstrated high prevalence of Rickettsia felis infection in patients in Bangladesh with unidentified febrile illness and suggests that this infection is endemic to the north-central area of this country. Females are more prone to get infected and most commonly noticed associated features was headache. Bangladesh Journal of Medical Microbiology, July 2023;17 (2):71-76 <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />